Pragmatika - funkcional'naâ perspektiva âzyka - Baranov, Anatolij G. (Stylistyka, 2021)
The dynamie chaos theory applied to linguistics casts light on the role of Perm school of functional stylistics (M.N. Kozhina) as an odd attractor promoting the study of text in dynamics, especially the functional stylistic-semantic categories of text. It is argued here that modem situation in linguistics is shaped by the application of global context (individual cognitive system - on the personal level, and culture in all its heterogeneity - on the social level) to the mainstream research of language in use. This methodological demand is met by functional pragmatics as whole semiotics embracing all aspects of semiosis. lt ensures the blend of cognitive and interpretive models with their specific procedures in revealing the subtleties of language in use. That is exemplified in the analysis of a chunk of fictive text. Besides, we set forth the category of tonality which denotes attitudes and tones permeating discourse, in the light ofM.N. Kozhina's contribution to the field.